2014
DOI: 10.1093/hmg/ddu555
|View full text |Cite
|
Sign up to set email alerts
|

A founder CEP120 mutation in Jeune asphyxiating thoracic dystrophy expands the role of centriolar proteins in skeletal ciliopathies

Abstract: Jeune asphyxiating thoracic dystrophy (JATD) is a skeletal dysplasia characterized by a small thoracic cage and a range of skeletal and extra-skeletal anomalies. JATD is genetically heterogeneous with at least nine genes identified, all encoding ciliary proteins, hence the classification of JATD as a skeletal ciliopathy. Consistent with the observation that the heterogeneous molecular basis of JATD has not been fully determined yet, we have identified two consanguineous Saudi families segregating JATD who shar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
75
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 34 publications
1
75
0
2
Order By: Relevance
“…Although patients with Joubert with KIAA0586 mutations have not been reported with findings of Jeune syndrome,23 there are other precedents for the coexistence of clinical characteristics of Joubert and Jeune syndromes. The chicken talpid 3 mutant displayed a small chest and developed extremely short limbs with increased number of digits, many of which were morphologically identical 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although patients with Joubert with KIAA0586 mutations have not been reported with findings of Jeune syndrome,23 there are other precedents for the coexistence of clinical characteristics of Joubert and Jeune syndromes. The chicken talpid 3 mutant displayed a small chest and developed extremely short limbs with increased number of digits, many of which were morphologically identical 1.…”
Section: Discussionmentioning
confidence: 99%
“…In human beings, mutations in CSPP1, a spindle pole-associated protein like KIAA0586, involved in the centrosome, were recently identified in patients with Joubert syndrome with features of Jeune syndrome 24 25. Finally, the product of CEP120 , mutated in some patients with Jeune syndrome,23 interacts with KIAA0586 26. In mice, the localisation of Cep120 to daughter centrioles27 is dependent on Talpid3 26.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mutations in two genes, CSPP1 and KIAA0586 , were reported to cause both JS and JATD, either isolated or in variable combination 24–31. Recently, a founder missense mutation of CEP120 (p.Ala199Pro) was identified in four Saudi Arabian families presenting the full-blown JATD phenotype, associated with cerebellar vermis hypoplasia in two patients and MTS in one of them 12. Remarkably, despite his Flemish origin without Arabian ancestors, one fetus in the present study (SW-476410) was found to carry the same founder mutation in combination with a nonsense mutation, leading to the hypothesis that this particular mutation might predispose to the development of skeletal defects.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, mutations in only a subset of the genes encoding IFT‐B complex members, IFT80 (Cavalcanti et al., ), IFT172 (Halbritter et al., ), IFT52 (Zhang et al., ), and IFT81 (Duran, et al., ), have been identified among the skeletal ciliopathies. In addition, mutations in two genes ( EVC (Ruiz‐Perez et al., ), EVC2 (Galdzicka et al., )) that encode basal body proteins, the NEK1 kinase gene (Thiel et al., ) and the gene encoding its interacting protein C21ORF2 (McInerney‐Leo et al., ; Wheway et al., ), the ICK MAP‐like kinase gene (Taylor et al., ), the INTU planar cell polarity (PCP) gene (Toriyama et al., ), the KIAA0586 (Alby et al., ) centrosomal protein gene, and the CEP120 core centriolar protein gene (Shaheen et al., ) have also been reported. Mutations in several of these genes, including the latter five genes, are rare causes of skeletal ciliopathies, each having been observed in only one or a few families.…”
Section: Introductionmentioning
confidence: 99%